2008
DOI: 10.1007/s10964-008-9286-7
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Adolescents’ Perceptions of Relationships with Their Parents

Abstract: This 4-wave longitudinal study examines developmental changes in adolescents' perceptions of parent-adolescent relationships by assessing parental support, conflict with parents, and parental power. A total of 951 early adolescents (50.4% boys) and 390 middle adolescents (43.3% boys) participated. Univariate and multivariate growth curve analyses showed that support declined from early to middle adolescence for boys and girls and increased from middle to late adolescence for girls, while stabilizing for boys. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
346
5
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 410 publications
(392 citation statements)
references
References 49 publications
32
346
5
9
Order By: Relevance
“…Previous studies have found that younger adolescent boys and girls perceive more support from both their mother and their father than older adolescents do (Bellerose et al, 2001;De Goede, Branje, & Meeus, 2009;Meeus, Iedema, Maassen, & Engels, 2005;Rey, Bird, KopecSchrader, & Richards, 1993). Nonetheless, from middle adolescence to late adolescence, perceived emotional support may stabilize, although De Goede et al (2009) report that it appears to increase slightly among girls in their study.…”
Section: Factors Influencing Parental Emotional Support and Controlmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have found that younger adolescent boys and girls perceive more support from both their mother and their father than older adolescents do (Bellerose et al, 2001;De Goede, Branje, & Meeus, 2009;Meeus, Iedema, Maassen, & Engels, 2005;Rey, Bird, KopecSchrader, & Richards, 1993). Nonetheless, from middle adolescence to late adolescence, perceived emotional support may stabilize, although De Goede et al (2009) report that it appears to increase slightly among girls in their study.…”
Section: Factors Influencing Parental Emotional Support and Controlmentioning
confidence: 96%
“…Overall, results of previous studies suggest that adolescents' perceptions of their parents' coercive control and emotional support change over time. More studies are thus needed to better understand these changes in various relationship characteristics (De Goede et al, 2009). …”
Section: Factors Influencing Parental Emotional Support and Controlmentioning
confidence: 99%
“…Relationship dynamics change between parents and children during their transition out of adolescence, with parent-child relationships becoming more egalitarian and less conflicted (De Goede et al, 2009;Furman and Buhrmester, 1992). It is unclear whether this general trend toward a more hands-off parenting approach will translate into less family conflict among families with emerging adults who are using substances and present for treatment.…”
Section: What Is Emerging Adulthood?mentioning
confidence: 99%
“…Indeed, adolescents report that they have more conflicts with their parents than with their friends (Adams and Laursen 2001;Furman and Buhrmester 1992;Jensen-Campbell and Graziano 2000). Also, whereas conflict with friends has been found to decline during adolescence (Collins and Laursen 1992), conflict with parents temporarily increases during early adolescence (for a review, see Collins and Steinberg 2006;De Goede et al 2008;McGue et al 2005), even though most parent-adolescent relationships remain close (Holmbeck 1996;Smetana et al 2006). In line with the social relational model, a meta-analysis on conflict management with close peers (defined as friends and romantic partners) and parents (Laursen 1993a) showed that adolescents used more negotiation with close peers than either disengagement (characterized by withdrawal or stand-off) and power assertion (defined as demanding behavior until the other person submits).…”
Section: Introductionmentioning
confidence: 99%